PERCENTAGE OF WEIGHT INCREASE IN EUROPEAN SPRUCE WOOD (PICEA ABIES.MILL), IMPREGNATED WITH POLYURETHANE AND ACRYLIC COATINGS - Mihajlovski Nikola; Konstantin Bahchevandjiev (University of Bihać - Faculty of Technical Engineering, 2013)
Impregnating and coating of wood with film forming materials are methods for the surface treatment of wood. Through the method of double vacuum (engl. Double vacuum process) polymeric film forming materials are incorporated into cellular and intracellular cavities of the surface layers of the wood. The resulting percentage of increase in mass (engl. Weight Percent Gain- WPG) is significantly larger than on classical coated wood. The progress rate of increase in mass of the test pieces, the impregnation with polyurethane coating is 11.4% and the impregnation with acrylic coating 10.6%. Differences in impregnated wood with polyurethane and acrylic coating are not statistically significant.
Keywords: impregnation, coating, european spruce, polyurethane coating, acrylic coating, weight percent gain